COMPARATIVE ANALYSIS OF CAMELS AND RGEC METHODS IN ASSESSING THE LEVEL OF HEALTH OF PT. BANK PANIN DUBAI SYARIAH TBK - rusdi rusdi; armyn hasibuan; damri batubara (Institut Agama Islam Negeri Padangsidimpuan, 2022)
Banks As intermediary institutions have a very important role in driving the economy in Indonesia, so banks must be managed very carefully and need special supervision from the government. The bank's health assessment method continues to grow, there are two new bank health assessment methods namely CAMELS and RGEC. This study aims to compare the CAMELS and RGEC methods in assessing the soundness of PT. Bank Panin Dubai Syariah Tbk in 2014-2018. This research is quantitative research. The population of this study is the financial statements of PT. Bank Panin Dubai Syariah Tbk. The sample of this study is the financial statements of PT. Panin Bank Dubai Syariah Tbk 2014-2018. The analysis technique used is a descriptive analysis using the CAMELS and RGEC methods. The results of this study note that the assessment of bank health by the CAMELS and RGEC methods has different results. The CAMELS method is more focused on achieving profit and growth, while the RGEC method focuses on a combination of self-assessment that emphasizes risk management, GCG implementation, and financial ratios that measure the condition of a bank. So that the RGEC Method becomes a more comprehensive bank health assessment solution.